Performance of steel reinforced high strength concrete investigated in the gas gun experiment - Jiang, G.; Huan, S.; Hao, Hong; Du, Y.; Jiao, C. (2013)
The shock properties of C100 concrete are investigated by gas gun planar impact technique. The manganin pressure gauge is used to measure the pressure-time curves of the samples. The physical quantities are all obtained by the Lagrange method. Moreover, it is observed from the measured pressure-time curves that the decay factor is smaller in the steel reinforced high strength concrete. The dynamic response is analyzed.